Safety Match Design Method and Experimental Study of the Chain Drive in Transfer Case - Wang Hongjun; Xu Shuxin; Ye Bin; Xing Jianheng (Jixie chuandong)
Based on the dynamic performance of the vehicle on the time sharing drive transmission and the full time drive transmission,the matching calculation of the chain drive in transfer case is studied. The calculating method of the load on chain in the transfer case under various typical conditions is analyzed. Accordingly,the design method of security matching is proposed,a test method of chain drive is introduced and the test result is analyzed,and the transfer case matching selection design example is listed. Results show that,under the condition of satisfy the premise of the power distribution of automobile transfer case,the fatigue performance and wear performance of the chain drive system can be guaranteed by the method of automobile transfer case chain matching design. It has the important guiding significance for the independent development of four- wheel drive in the transfer case chain drive system field.